Failure of Decidualization and Maternal Immune Tolerance Underlies Uterovascular Resistance in Intra Uterine Growth Restriction - Dunk, Caroline; Kwan, Melissa; Hazan, Aleah; Walker, Sierra; Wright, Julie K.; Harris, Lynda K.; Jones, Rebecca Lee; Keating, Sarah; Kingdom, John C. P.; Whittle, Wendy; Maxwell, Cynthia; Lye, Stephen J. (Frontiers in Endocrinology, 2019)
Failure of uterine vascular transformation is associated with pregnancy complications including Intra Uterine Growth Restriction (IUGR). The decidua and its immune cell populations play a key role in the earliest stages of this process. Here we investigate the hypothesis that abnormal decidualization and failure of maternal immune tolerance in the second trimester may underlie the uteroplacental pathology of IUGR. Placental bed biopsies were obtained from women undergoing elective caesarian delivery of a healthy term pregnancy, an IUGR pregnancy or a pregnancy complicated by both IUGR and preeclampsia. Decidual tissues were also collected from second trimester terminations from women with either normal or high uterine artery Doppler pulsatile index (PI). Immunohistochemical image analysis and flow cytometry were used to quantify vascular remodeling, decidual leukocytes and decidual status in cases versus controls. Biopsies from pregnancies complicated by severe IUGR with a high uterine artery pulsatile index (PI) displayed a lack of: myometrial vascular transformation, interstitial and endovascular extravillous trophoblast (EVT) invasion, and a lower number of maternal leukocytes. Apoptotic mural EVT were observed in association with mature dendritic cells and T cells in the IUGR samples. 2nd trimester pregnancies with high uterine artery PI displayed a higher incidence of small for gestational age fetuses; a skewed decidual immunology with higher numbers of; CD8 T cells, mature CD83 dendritic cells and lymphatic vessels that were packed with decidual leukocytes. The decidual stromal cells failed to differentiate into the large secretory DSC in these cases, remaining small and cuboidal and expressing lower levels of the nuclear progesterone receptor isoform B, and decidual stromal cell markers Insulin Growth Factor Binding protein-1 (IGFBP-1) and CD10 as compared to controls. This study shows that defective progesterone mediated decidualization and a hostile maternal immune response against the invading endovascular EVT contribute to the failure of uterovascular remodelling in IUGR pregnancies.